Combined Scutellarin and C18H17NO6 Imperils the Survival of Glioma: Partly Associated With the Repression of PSEN1/PI3K-AKT Signaling Axis - He, Xiu-Ying; Xu, Yang; Xia, Qing-Jie; Zhao, Xiao-Ming; Li, Shan; He, Xiao-Qiong; Wang, Ru-Rong; Wang, Ting-Hua (Frontiers in Oncology, 2021)
Glioma, the most common intracranial tumors, harbors great harm. Since the treatment for it has reached the bottleneck stage, the development of new drugs becomes a trend. Therefore, we focus on the effect of scutellarin (SCU) and its combination with C18H17NO6 (abbreviated as combination) on glioma and its possible mechanism in this study. Firstly, SCU and C18H17NO6 both suppressed the proliferation of U251 and LN229 cells in a dose-dependent manner, and C18H17NO6 augmented the inhibition effect of SCU on U251 and LN229 cells in vitro. Moreover, there was an interactive effect between them. Secondly, SCU and C18H17NO6 decreased U251 cells in G2 phase and LN229 cells in G2 and S phase, but increased U251 cells in S phase, respectively. Meanwhile, the combination could further reduce U251 cells in G2 phase and LN229 cells in G2 and S phase. Thirdly, SCU and C18H17NO6 both induced the apoptosis of U251 and LN229. The combination further increased the apoptosis rate of both cells compared with the two drugs alone. Furthermore, SCU and C18H17NO6 both inhibited the lateral and vertical migration of both cells, which was further repressed by the combination. More importantly, the effect of SCU and the combination was better than positive control-temozolomide, and the toxicity was low. Additionally, SCU and C18H17NO6 could suppress the growth of glioma in vivo, and the effect of combination was better. Finally, SCU and the combination upregulated the presenilin 1 (PSEN1) level, but inactivated the PI3K-AKT signaling in vitro and in vivo. Accordingly, we concluded that scutellarin and its combination with C18H17NO6 suppressed the proliferation/growth and migration, and induced the apoptosis of glioma, in which the mechanism might be associated with the repression of PSEN1/PI3K-AKT signaling axis.